2011
DOI: 10.1007/s10815-011-9678-6
|View full text |Cite
|
Sign up to set email alerts
|

Implantation rates of embryos generated from slow cooled human oocytes from young women are comparable to those of fresh and frozen embryos from the same age group

Abstract: Previous reports of slow cooling of human mature oocytes have shown a reduced clinical efficiency relative to fresh oocytes. This study reports that equivalent fertilization and implantation rates to those obtained using fresh oocytes and cryopreserved embryos can be achieved with human mature oocytes dehydrated in 1.5 M propanediol and 0.2 M sucrose at 37°C and cryopreserved using slow cooling rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
0
4
1
Order By: Relevance
“…Although the fertilisation rate in the present study is lower than previously reported for our fresh oocytes and slow frozen oocytes [38], this is probably due to the change from use of donor sperm in cases of failed testicular retrieval [38] to fertilisation with testicular sperm obtained from repeated attempts at testicular biopsy in the majority of cases in the present study. The fertilisation rate for fresh oocytes using testicular sperm in our clinic during the same time period is 61.4 % (1227/1998).…”
Section: Discussioncontrasting
confidence: 86%
“…Although the fertilisation rate in the present study is lower than previously reported for our fresh oocytes and slow frozen oocytes [38], this is probably due to the change from use of donor sperm in cases of failed testicular retrieval [38] to fertilisation with testicular sperm obtained from repeated attempts at testicular biopsy in the majority of cases in the present study. The fertilisation rate for fresh oocytes using testicular sperm in our clinic during the same time period is 61.4 % (1227/1998).…”
Section: Discussioncontrasting
confidence: 86%
“…This slow-cooling protocol maintains the survival, fertilization, cleavage rates and embryo quality reported for previous protocols (Fabbri et al, 2001;Gook and Edgar, 2011) while pregnancy and implantation rate are significantly improved. Oocyte slow freezing performed with a modified protocol can give good and consistent outcomes.…”
Section: Clinical Outcomes With Slow Freezingmentioning
confidence: 67%
“…However, CPA loading takes longer at reduced temperatures due to decreased membrane permeability [57; 72]; the extended exposure to CPA in the loading solution may, paradoxically, increase damage caused by chemical cytotoxicity. Alternatively, it might be possible to minimize the toxicity effects by loading penetrating CPAs at modestly elevated temperatures, thus minimizing the duration of CPA exposure [26]. This approach offers additional benefits in terms of avoiding chilling injury.…”
Section: Discussionmentioning
confidence: 99%